2021
DOI: 10.1088/1741-4326/abecc8
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence suppression by energetic particles: a sensitivity-driven dimension-adaptive sparse grid framework for discharge optimization

Abstract: A newly developed sensitivity-driven approach is employed to study the role of energetic particles in suppressing turbulence-inducing micro-instabilities for a set of realistic JET-like cases with NBI deuterium and ICRH 3He fast ions. First, the efficiency of the sensitivity-driven approach is showcased for scans in a 21-dimensional parameter space, for which only 250 simulations are necessary. The same scan performed with traditional Cartesian grids with only two points in each of the 21 dimensions would requ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Moreover, ascertaining the impact of variations in parameters that characterize the confining magnetic field is crucial as well (e.g., for design optimization). We note that the current sparse grid framework has been employed for UQ and SA in linear simulations in fusion research (linear in the five phase-space variables that characterize the underlying gyrokinetic model) in previous efforts 13 , 32 . Linear simulations are often used to gain valuable insights regarding some general trends or parameter dependencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ascertaining the impact of variations in parameters that characterize the confining magnetic field is crucial as well (e.g., for design optimization). We note that the current sparse grid framework has been employed for UQ and SA in linear simulations in fusion research (linear in the five phase-space variables that characterize the underlying gyrokinetic model) in previous efforts 13 , 32 . Linear simulations are often used to gain valuable insights regarding some general trends or parameter dependencies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it intrinsically provided an accurate interpolation-based surrogate model of the parameters-to-output of interest mapping that was nine orders of magnitude cheaper than the high-fidelity model. Note that in the context of the simpler linear gyrokinetic simulations concerning turbulence suppression by energetic particles, recent research efforts have shown that the sensitivity-driven approach can be effectively used as a surrogate model for optimization 32 or as a low-fidelity model in a multi-fidelity study 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This reduced model can be further used, for example, for optimization purposes or as a low-fidelity model in a subsequent multi-fidelity UQ study. Note note that in the context of the simpler linear gyrokinetic simulations concerning turbulence suppression by energetic particles, we have recently showed that the sensitivity-driven approach can be effectively used as surrogate model for optimization [12] or as a low-fidelity model in a multi-fidelity study [22].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fast ions can affect plasma turbulence in turn [13][14][15]. In some experimental and numerical studies [16][17][18][19][20], the suppression of plasma turbulence has also been observed, which is linked to the presence of fast ions. Generally, the effects of fast ions can be classified as electrostatic effects and electromagnetic effects.…”
Section: Introductionmentioning
confidence: 99%